PRIMARY SCHOOL PRE-SERVICE TEACHERS PERSPECTIVES ON PRIMARY YEARS PROGRAM AND ITS IMPLEMENTATION - Theresia Yunia Setyawan (IJIET (International Journal of Indonesian Education and Teaching), 2017)
As one of the most widely used international primary curricula in the world, the Primary Years Program (PYP) introduced by the International Baccalaureate Organization (IBO) has significantly increased its number of world schools in the Asia Pacific region including Indonesia. With the increased number of IB World Schools in the country, there comes a need to prepare for teachers qualified for teaching using the PYP as their framework. Indonesian higher educational institutions are therefore required to not only prepare teachers qualified in their teaching profession but also those having an open mind towards international education in general. It is important, then, to have insights on what these pre-service teachers think about international primary education, especially about the PYP and its implementation in primary schools in Indonesia. These perspectives will make useful raw data on the characteristics of Indonesian primary pre-service teachers and their readiness to take their professional career in any international primary schools including the IB world schools.doi.org/10.24071/ijiet.2017.010105